THE RELATIONSHIP BETWEEN THE CAUSES OF CHRONIC ENERGY DEFICIENCY (KEK) AND THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN AT THE SIDOTOPO PUBLIC HEALTH CENTER, SURABAYA - Eka Widya novika Sari (Health Notions, 2022)
Chronic Energy Deficiency is a nutritional status one experiences an imbalance caused by a lack of consuming energy sources containing the nutritional substances the body needs. Chronic Energy Deficiency is one of the factors that affect the incidence of anemia in pregnant women. In Sidotopo Public Health Center in 2018, there were 87,71% of pregnant women had anemia and 40,94% had a Chronic Energy Deficiency. The purpose of the study is to figure out the relationship between the causative factors of Chronic Energy Deficiency with the incidence of anemia in pregnant women. This type of Research is analytic research with a cross-sectional approach. His data collection instruments use data collection sheets. Using chi-square test with ɑ = 0.05. The results of the study were obtained that most of the causative factors of Chronic Energy Deficiency can cause anemia incidence in pregnant women. Based on statistical tests using chi-square test, age factor obtained p=0,020<ɑ=0,05, education p=0.264<ɑ=0.05, parity p=0.022<ɑ=0.05, pregnancy distance p=0.001<ɑ=0.05, family income p=0.550<ɑ=0.05, nutritional status p=0,000<ɑ=0.05. The causative factors of Chronic Energy Deficiency are associated with the incidence of anemia namely age factors, parity, pregnancy distance, nutritional status. Attempts to maintain and improve the nutritional status of pregnant women can go through counseling, Antenatal Care supervision, giving food supplements (PMT), whereas prevention and coping anemia need supervision in blood added tablets (TTD) administration of at least 90 tablets in pregnant women.